The experiment research and engineering verification on the synergistic lubrication properties of silver and multiwalled carbon nanotubes. (September 2019) - Yang, Kang; Ma, Hongru; Ma, Ming; Lin, Haibo; Li, Xiaoxue
A synergistic lubrication of silver and multiwalled carbon nanotubes was studied to minimize friction and decrease wear in the rotating mechanical components. Samples of TiAl alloy (TA), TiAl–10 wt% Ag (TAA), and TiAl–10 wt% Ag–1.0 wt% multiwalled carbon nanotubes (TAAM) were prepared using spark plasma sintering. The method of experimental test and engineered verification was used to explore the synergistic lubrication of silver and multiwalled carbon nanotubes in the TAAM sliding against Si3 N4 balls on the ball-on-disk tribometer of No. HT-1000. The results showed that the friction and wear behavior of the TAA was more excellent than that of a TA. The TAAM obtained the smaller friction coefficient and wear rate in comparison to the TAA. The multiwalled carbon nanotubes were pulled out of the TAAM during sliding, were exposed on a wear scar, and were tightly combined with the silver to form a lubrication film. The lubrication film with silver and multiwalled carbon nanotubes resulted in an excellent friction reduction and wear-resistant property, and it caused the TAAM to obtain smaller friction and lower wear than those of the TA and TAA.